(untitled) (Global Journal of Science Frontier Research, 2019)
Wadi Jararah-Wadi Kharit is considered a large area located in the southeastern desert of Egypt with approximately 38,000 Km2 coverage extensions. The geologic outcrops of the area show a wide range of stratigraphic rock units from Precambrian to Quaternary. The detection of litho logic surface coverage units and their relationships to the high-radioactivity zones and its characterizations are the main tasks of this article. An integration between airborne Gamma-ray spectrometric data and Landsat 8 Operational Land Imager (OLI) satellite image has been used to determine and highlight the main radioactive zones covering the entire area of investigation; in addition to the relationship between airborne radioactive detected zones and their different kinds of related geologic alterations. The radioelement concentration values of the equivalent Uranium (eU), equivalent Thorium (eTh), and Potassium (K) successively discriminated several distinctive radioactive zones over Wadi Jararah-Wadi Kharit area. Fifteen main groups of statistically significant (anomalous) zones have been distinguished and show localities that represent uraniferous anomalous zones which could considered as a possible target of interest for ground follow-up investigation.